Augmenting an Inpatient Fall Program With Video Observation. Issue 1 (January 2021) - Davis, James E.; Carter-Templeton, Heather
Abstract : Background: Keeping patients safe is a goal for all health care facilities. Facilities should look at technology as a way to help improve outcomes. Patient falls are a dangerous, costly, and preventable health care–associated event. Local Problem: The fall rate on the host facility's orthopedic unit was 2.6 per 1000 patient-days. Methods: Patients on an inpatient orthopedic unit who had a fall risk score greater than 13, based on the Johns Hopkins Fall Risk Assessment Tool, were provided with an added intervention, video observation. Intervention: Video observation units with 2-way communication were introduced to help prevent patient falls. Results: The fall rate per 1000 patient-days after implementing this intervention for 6 weeks was 0 falls per 1000 patient-days. Conclusions: There was a 100% decrease in patient falls on the inpatient unit where video observation was implemented.